Correlation between upper limb functional ability and structural hand impairment in an early rheumatoid population. - Adams, J; Burridge, J; Mullee, M; Hammond, A; Cooper, C (2004)
OBJECTIVE: To explore the relationship in individuals with early rheumatoid arthritis (RA) between self-report upper limb function, therapist-assessed upper limb function and therapist-assessed measures of structural impairment (handgrip, active hand motion and metacarpophalangeal (MCP) joint ulnar deviation). DESIGN: Thirty-six patients with early RA were recruited across seven outpatient occupational therapy departments. OUTCOME MEASURES: Upper limb functional activity and ability was measured using the Disability of the Arm, Shoulder and Hand (DASH) questionnaire and the Grip Ability Test (GAT). Upper limb impairment was assessed by bilateral power handgrip using the MIE Digital Grip Analyser, goniometry measures of bilateral metacarpophalangeal (MCP) joint ulnar deviation and bilateral active motion of the wrist. RESULTS: Strong correlations (> 0.7) were seen between the self-report DASH questionnaire and the therapist-rated GAT assessment. Bilateral power handgrips were also strongly correlated with both functional assessments. Dominant ulnar deviation at the MCP joints demonstrated a weak correlation (0.3-0.4) with both self-report and therapist-rated functional ability and a weak to moderate. (0.1-0.5) correlation on the nondominant side. CONCLUSION: In this early RA population handgrip strength is an accurate indicator of upper limb ability. Ulnar deviation at the MCP joints shows only a weak to moderate association with upper limb functional activity and ability. Although the DASH and the GAT were strongly correlated, the DASH was a more discriminating measure than the GAT in assessing upper limb ability in this sample population.